Efecto de la aplicación de Calcio y Boro, sobre la calidad y rendimiento del fruto de Banano (Musa spp) en el cantón Baba, Provincia de Los Ríos - Pérez Santos, José Antonio (2017)
VII. SUMMARY The present research work was carried out in the properties of Hacienda Francia, belonging to the company "Agrovictoria S.A", located at km. 3,0 of the Baba-Salitre road (Recinto Progreso). The geographic coordinates (UTM) are X = -1.7723946 and Y = -79.7102593. The zone has an average temperature of 24 to 26 0C, relative humidity 88%, annual precipitation of 1262 mm and a height of 8 masl. The experimental work was carried out in an established banana plantation of the Valery variety, which is currently in production. The proposed objectives were to establish the effect of the application of Calcium and Boron on the quality and yield of the banana crop (Musa spp.); determine the best form of application (Sheets - Cluster) of the three products based on Calcium and Boron in the banana crop; quantify the effect of Calcium and Boron on the calibration and length of banana fruit and establish costs of each treatment based on yields. The treatments consisted of three products based on calcium and boron, such as Calcio 10% + Boro 0,3% in a dose of 1.00 L / ha; Calcio 30% + Boro 1% 0.30 kg / ha; Calcio 8% + Boro 1% 1.20 L / ha applied via foliar and cluster plus an absolute control without application of products. The Design of "Complete Random Blocks" was used, with seven treatments and three repetitions. To determine the statistical mean between treatments, the Tukey test at 95% probability was used. For the good development of the banana crop, the rules of crop management were respected, such as fertilization, phytosanitary control, irrigation and harvest. The data evaluated in the experimental work were number of leaves to the sheath and to the harvest; bunch weight, number of hands per bunch (hands / cluster), length and caliber of the middle finger of the second hand, length and caliber of the middle finger of the last hand, weight of the rachis, shrinkage (%),yield, fruit quality and economic analysis. For the exposed results it was determined that the highest number of leaves when sheathed was obtained by the application of Calcio 10% + Boro 0,3% to the cluster in a dose of 1.0 L / ha, while Calcio 30% + Boro 1% via foliar, in a dose of 0.30 kg / has influenced so that there are more leaves at harvest; the use of Calcio 8% + Boro 1% , applied to the cluster in doses of 1.20 L / ha, increased the weight of the bunch and the rachis; the treatment with the largest number of hands was when Calcio 10% + Boro 0,3% was used at a dose of 1.00 L / ha via foliar; using Calcio 8% + Boro 1% in a dose of 1.20 L / ha via foliar, greater length was obtained and a greater calibration was applied to the cluster of the middle finger of the second hand; the length and calibration of the middle finger of the last hand registered the highest average with the use of Calcio 30% + Boro 1% in the cluster, in a dose of 0.30 kg / ha; the use of Calcio 10% + Boro 0,3% , applied via foliar in doses of 1.00 L / ha reported a higher percentage of shrinkage and Calcio 8% + Boro 1% to the cluster in doses of 1.20 L / ha showed a higher ratio and the treatment that Calcio 8% + Boro 1% was applied to the cluster in a dose of 1.2 L / ha, it obtained higher yield, quality and profitable net profit of $ 12065.20 / ha / year.